Audio-visual video based circuit training model development design in futsal sports - Amiq, Fahrial; Setiyono, Hari; Nurhasan, Nurhasan; Lesmana, Heru Syarli; Jr, Procopio B. Dafun; Ayubi, Novadri; Robiansyah, Moh. Ferry (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
This study aimed to develop a circuit training model using audio-visual video media in futsal. The researcher used the R&D method. The subject possessed the characteristics of being male, aged between 20 and 30 years, with a Body Mass Index between 18 and 34, and was a futsal athlete. Before the study began, the researcher explained the research procedure, and the subjects filled out informed consent forms. This technique was used to analyze the data obtained from distributing questionnaires. Questionnaires were given to futsal experts, media experts, and coaching experts. The reliability test was carried out by 12 subjects from the small group test and 24 subjects from the large group test. The results of this development are in the form of videos; in these videos, there are 4 training models consisting of 4 posts each. The 4 posts are arranged in 1 round, with each post consisting of 3 athletes. In this training model, the athletes exercise at each post for 20 seconds; after completing one exercise model, they move to the next post. Exercises are done for 3 sets, with 1-minute recovery between sets. Based on the expert validity test, the evaluation results of futsal experts averaged 85.5%, media experts averaged 82.0%, and coaching experts averaged 83.3%. Furthermore, the results of the reliability test for the small group obtained a percentage of 88%, and for the large group, it was 87.87%. The development of a circuit training model in futsal games can help athletes become more enthusiastic and can also enable them to do additional exercises outside the schedule by using this video product as a training guide, providing athletes with many variations in their exercises.